TPACK-Based Social Internalization: Innovative Social Studies Praxis for Enhancing Social Literacy and Cognitive Skills at SMPN 11 Madiun - Henrykus Titis Sunarno; Moch Agus Setiono; Sukanan; Jinem (Universitas Negeri Surabaya, 2026)
While digital technology has become a staple in modern classrooms, its capacity to instill meaningful social values remains notably underdeveloped, particularly within the domain of social studies. This research seeks to bridge this gap by investigating an integration model underpinned by TPACK designed to bolster both social literacy and higher order thinking skills among students. Adopting a quantitative quasi experimental approach with a non equivalent control group design, the study focused on eighth grade students at a public junior high school in Madiun, Indonesia. Participants were selected via cluster random sampling and partitioned into experimental and control cohorts. Data, gathered through validated assessment instruments, underwent rigorous analysis using independent samples t tests. The empirical results demonstrate that the proposed model yields significantly better outcomes than traditional instructional methods in advancing both cognitive abilities and social proficiency (p < 0.05). A pivotal aspect of this model is its synthesis of the TPACK framework with the triadic process of social meaning construction, namely objectification, subjectification, and externalization, which facilitates the conversion of digital content into authentic social awareness. From a theoretical perspective, this research contributes to digital pedagogy oriented toward values by reimagining TPACK as a vehicle for social value formation rather than a mere framework for technical implementation. On a practical level, the model provides educators with a systematic blueprint for weaving essential social values into the fabric of digital learning environments.Keywords: TPACK, social internalization, social literacy, HOTS, digital pedagogy.